Correction of Low Neonatal Vitamin D Status Using 1000 IU/d of Vitamin D Improved Body Composition (Lean Mass and Fat Mass) Compared to Using the Standard of Care by 6 Months of Age (P11-094-19). (13th June 2019) - Razaghi, Maryam; Vanstone, Catherine; Sotunde, Olusola; Gharibeh, Nathalie; Kimmins, Sarah; Wei, Shuqin; McNally, Dayre; Rauch, Frank; Jones, Glenville; Weiler, Hope
Abstract: Objectives: Vitamin D status is positively associated with lean mass phenotype in healthy infants born with sufficient vitamin D stores. The objective is to test whether rapid correction of low neonatal vitamin D status improves body composition (lean mass and fat mass) at 6 mo of age. Methods: In a double-blinded randomized parallel group controlled trial (NCT02563015), healthy term neonates of appropriate weight for gestational age were recruited from Montreal. Capillary blood samples were collected 24–36 h post natally for measurement of serum 25-hydroxyvitamin D [25(OH)D] (Liaison, Diasorin Inc.). Infants with serum 25(OH)D < 50 nmol/L (n = 87) were randomized to receive 400 or 1000 IU/d until 6 mo of age. Those with 25(OH)D ≥ 50 nmol/L (n = 31) were recruited as a reference group, and received 400 IU/d. Anthropometry, lean mass and fat mass (dual-energy x-ray absorptiometry) were measured at baseline, 3 and 6 mo. Skin color was measured using a spectrophotometer. Differences between treatments and reference groups were tested using mixed model and repeated measures ANOVA accounting for the effects of sex, season of birth, skin color and gestational age (GA). Results: Neonates (67 males, 51 females) were 39.6 ± 1wk GA and 3387 ± 371 g at birth. There were no differences between groups in lean mass or fat mass at baseline; nor in weight or length at any time-point. Combined treatment groups, had lower serum 25(OH)D concentrations at birth compared to the reference group (33 ± 11 vs. 69 ± 13 nmol/L, P  < 0.0001). However, at 6 mo of age, serum 25(OH)D concentration was higher in the group receiving 1000 IU/d (n = 34), in comparison to the group receiving 400 IU/d (n = 29), and the reference (n = 19) group (125.0 ± 34.0, 82.2 ± 21.5 vs. reference 85.4 ± 32.1 nmol/L, P  < 0.0001). Whole body lean mass was significantly different among groups (5071.3 ± 750.0, 4944.1 ± 616.3 and 5166.0 ± 645.4 g, respectively, P  = 0.03), with infants in the treatment group provided a 400 IU/d supplement having a lower lean mass by 6 mo of age compared to the 1000 IU/d group. Fat mass was not different among groups following post-hoc testing (2967.0 ± 929.0 and 2962.0 ± 952.0, 2742.0 ± 754.0 g, P  = 0.16). Conclusions: Higher dosage supplementation of vitamin D rapidly improved vitamin D status and supported a leaner body phenotype in infancy. Funding Sources: Canadian Institutes of Health Research.